2020
DOI: 10.1177/0017896920949600
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health education infographics in Saudi Arabia

Abstract: Objective: To evaluate the health education infographics posted on Twitter accounts by major health care institutions in Saudi Arabia. Method: Cross-sectional review of health education infographics using a semi-structured evaluation form. The scoring rubric included 10 criteria grouped under 4 main headings: (1) usefulness, (2) legibility, (3) graphics and illustrations and (4) aesthetics. Rated on a scale of 1 to 5, scored items were summed and converted into a percentage. Each infographic was classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…They found that after the intervention the grade value was higher and 93.75% of the students considered it a useful tool (Vega‐Garzón et al, 2022 ). In the same way, other research groups conducted a study of infographics in health education in Saudi Arabia and concluded that they were of high quality and recommended designing and making infographics on public health and using it through social networks (Jahan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that after the intervention the grade value was higher and 93.75% of the students considered it a useful tool (Vega‐Garzón et al, 2022 ). In the same way, other research groups conducted a study of infographics in health education in Saudi Arabia and concluded that they were of high quality and recommended designing and making infographics on public health and using it through social networks (Jahan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An infographic is not complete without references, as these add validity and credibility for both a lay and medical audience. In Saudi Arabia, Jahan et al 30 assessed 297 infographics on chronic health conditions for patients created by healthcare institutions, and none had references. References provide clinicians with the option to acquire more detailed information, before making changes to clinical practice.…”
Section: Keeping Infographics Evidence-basedmentioning
confidence: 99%
“…The message's effectiveness is determined not just by the integrity of the information but also by how entertaining the information is presented. As a result, there is a need for collaboration between social media designers and health education specialists (Jahan et al, 2021).…”
Section: Health Professionals and The Use Of Infographicsmentioning
confidence: 99%